2013
DOI: 10.1038/nm.3089
|View full text |Cite
|
Sign up to set email alerts
|

Randomized dose-finding clinical trial of oncolytic immunotherapeutic vaccinia JX-594 in liver cancer

Abstract: Oncolytic viruses and active immunotherapeutics have complementary mechanisms of action (MOA) that are both self amplifying in tumors, yet the impact of dose on subject outcome is unclear. JX-594 (Pexa-Vec) is an oncolytic and immunotherapeutic vaccinia virus. To determine the optimal JX-594 dose in subjects with advanced hepatocellular carcinoma (HCC), we conducted a randomized phase 2 dose-finding trial (n = 30). Radiologists infused low-or high-dose JX-594 into liver tumors (days 1, 15 and 29); infusions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
599
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 682 publications
(615 citation statements)
references
References 25 publications
7
599
3
6
Order By: Relevance
“…Recently, sipuleucel-T (Provenge, Dendreon, Seattle, WA, USA), indicated for patients with metastatic castration-resistant prostate cancer, received FDA's approval as the first therapeutic cancer vaccine. 5 In addition, extensive Phase II clinical trials have demonstrated that the oncolytic herpes simplex virus talimogene laherparepvec (T-Vec, Amgen Inc., Thousand Oaks, CA, USA) 6 and vaccinia virus JX-547 (Pexa-Vec, Jennerex Biotherapeutics, Inc., San Francisco, CA, USA), 7 both of which carry the gene encoding the immunostimulatory cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), hold great promise for the treatment of advanced cancer patients. Furthermore, cytotoxic T-cell responses directed against oncolytic virus-infected cancer cells have been identified as an essential factor in the process of destruction of cancer.…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sipuleucel-T (Provenge, Dendreon, Seattle, WA, USA), indicated for patients with metastatic castration-resistant prostate cancer, received FDA's approval as the first therapeutic cancer vaccine. 5 In addition, extensive Phase II clinical trials have demonstrated that the oncolytic herpes simplex virus talimogene laherparepvec (T-Vec, Amgen Inc., Thousand Oaks, CA, USA) 6 and vaccinia virus JX-547 (Pexa-Vec, Jennerex Biotherapeutics, Inc., San Francisco, CA, USA), 7 both of which carry the gene encoding the immunostimulatory cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), hold great promise for the treatment of advanced cancer patients. Furthermore, cytotoxic T-cell responses directed against oncolytic virus-infected cancer cells have been identified as an essential factor in the process of destruction of cancer.…”
Section: Open Questionsmentioning
confidence: 99%
“…Indeed, the results of clinical trials of the GM-CSF gene-harboring oncolytic vaccinia virus JX-594 and the GM-CSF gene-harboring oncolytic herpes virus talimogene laherparepvec demonstrated that a clinical benefit can be accomplished by combined respective oncolytic activity with the recruitment of immune cells. 6,7,131 The combination of adoptive T-cell therapy with oncolytic viruses is shown to elicit an increased antitumor effect. 131,132 Collectively, the design of combinatorial therapies of oncolytic viruses with immunotherapeutic modalities may 136,137 and (6) directly targets not only the primary tumor but also metastases.…”
Section: Strategies To Enhance the Potentials Of Icd Induced By Oncolmentioning
confidence: 99%
“…Emerging therapies: Recently, the oncolytic and immunotherapeutic vaccinia virus has been reported to induce antibody-mediated, complement-dependent cancer cell lysis in humans [116] . Immunotherapy may benefit patients with advanced stage HCC who do not have further treatment options.…”
Section: Radiotherapies and Emerging Therapiesmentioning
confidence: 99%
“…2). While promising early-and late-phase clinical trials employing OVs to treat cancers continue to generate great enthusiasm, heterogeneity in clinical response remains a challenge [2][3][4] . To this end, it has been long recognized that improvements to therapeutic efficacy either through viral engineering or through combination therapies will be critical to the success of these platforms 2,5 .…”
mentioning
confidence: 99%